Developing an online micro-credential course on good prescribing skill for undergraduate medical students / Mohd Huzaimi Haron ... [et al.] - Haron, Mohd Huzaimi; Razali, Norhafiza; Kamarudin, Siti Norsyafika; Ab Azis, Norasikin; Abdul Nasir, Nurul Alimah; Mohd Ismail, Nafeeza; Abu Hanipah, Noor Fahitah (Universiti Teknologi MARA, 2025)
Prescribing errors are known to account for a substantial proportion of all medication errors which could lead to morbidity and mortality of patients in clinical settings. Considering the number of deaths due to prescribing error, many developed countries such as the United Kingdom have commenced educational assessment to enforce good prescribing techniques to all medical graduates before they start their clinical practice. However, in Malaysia, there is no standardised or specific curriculum or programme that enforces the understanding of prescribing skills and its safety to the undergraduates. As a result, high prescribing errors were seen among housemen and junior medical officers. In view of the current curriculum and related problems, an online micro-credential course on ‘Guide to Good Prescribing Skill’ was developed by the members of Department of Pharmacology, Faculty of Medicine, UiTM to fill the gap. This paper describes the course development. The course covers the theory behind the importance of good prescribing skills as recommended by WHO and the steps to prescribe drugs according to patient diagnosis. The development of this prescribing skill module will help in giving a structured learning experience to medical students and may improve their readiness and competency when starting real clinical practice after graduation. It is hoped that this course will be an effective way of learning prescribing skills and serve to prevent errors in clinical practice.